Catheterization Without Supination—A Series of 36 Prone Position Internal Jugular Vein Cannulations. (30th December 2022) - Lussier, Bethany L.; Pham, David T.; Ratti, Gregory A.; Patel, Jiten; Mitchell, Brandon C.; Chen, Catherine
Abstract : OBJECTIVES: Describe the clinical characteristics and outcomes of 32 critically ill patients who underwent central venous cannulation of the internal jugular vein while in prone position. DESIGN: Retrospective cohort analysis. SETTING: Single tertiary-care urban academic safety-net hospital. PATIENTS/SUBJECTS: Patients requiring mechanical ventilation and prone positioning for severe acute respiratory distress syndrome from March 1, 2020, through March 31, 2021. INTERVENTIONS: Internal jugular vein cannulation while in the prone position. MEASUREMENTS AND MAIN RESULTS: The technique used for venous access, procedural complications, patient demographics, and clinical outcomes are described. Thirty-six prone internal jugular vein cannulations for 32 hemodialysis catheters and four central venous catheters were successfully performed in 32 patients. One immediate and one delayed pneumothorax occurred. Inhospital mortality was 88%. CONCLUSIONS: In the largest series to date, cannulation of the internal jugular vein with the patient in prone position is feasible but associated with a 6% risk of pneumothorax. Severity of illness in patients intolerant of supine positioning results in high inhospital mortality.